2000
DOI: 10.1002/1096-8628(20000612)96:3<310::aid-ajmg15>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Association study of the tryptophan hydroxylase gene and bipolar affective disorder using family-based internal controls

Abstract: The tryptophan hydroxylase (TPH) gene encodes for the rate-limiting enzyme of the serotonin metabolism and, therefore, has to be considered a major candidate for association studies in affective disorders. Recently, an association between this gene and bipolar affective disorder has been reported in a French population. We sought to replicate this finding in a German sample. Allele frequencies of a biallelic polymorphism (A218C) of the TPH gene were determined in 95 bipolar I patients and their parents. Prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The present study demonstrated no association of distribution of TPH1 A218C gene polymorphism with UPD in Han Chinese, in accordance with the studies in bipolar affective disorders in German (19) and in depressed Japanese patients with suicidal intentions (20). The results were only partially consistent with the study by Du et al (21), where there was no association of distribution of TPH1 A218C polymorphism with UPD, but there was an obvious association between TPH1 A218C and somatoform in severely depressed Caucasian patients, and the patients with A allele and A/A genotype had higher scores of somatoform.…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated no association of distribution of TPH1 A218C gene polymorphism with UPD in Han Chinese, in accordance with the studies in bipolar affective disorders in German (19) and in depressed Japanese patients with suicidal intentions (20). The results were only partially consistent with the study by Du et al (21), where there was no association of distribution of TPH1 A218C polymorphism with UPD, but there was an obvious association between TPH1 A218C and somatoform in severely depressed Caucasian patients, and the patients with A allele and A/A genotype had higher scores of somatoform.…”
Section: Discussionsupporting
confidence: 92%
“…-The functional polymorphism in the upstream regulatory region of the SERTPR also analysed by Mundo et al (2001) -Two serotonin receptor 2A (5-HT 2A ) polymorphisms (T102C and C-1420T) [ (Chee et al 2001;Ni et al 2002;Ranade et al 2003)] -The tryptophan hydroxylase (TPH) A218C substitution (Ho et al 2000;Rietschel et al 2000) -The beta subunit of G-proteins gene (Gbeta3) C825T polymorphism (Chen et al 1996;Lin et al 2001) -A polymorphism located in the third exon of the dopamine D4 receptor (DRD4) gene (Muglia et al 2002) -The dopamine receptor 2 (DRD2) S311C gene variant (Massat et al 2002) -The COMT Met158 polymorphism (Mynett-Johnson et al 1998;Papolos et al 1998) -A polymorphism located 1.2 kb upstream of the MAO-A coding sequences (Preisig et al 2000) Materials and methods…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies in this study were different from those found by Bellivier et al 33 This was the only report where an overall association of TPH*A with bipolar disorder was observed while several others failed to confirm this finding. [34][35][36][37][38][39][40] TPH variants have also been associated with alcoholism, 41 but further rare variants did not prove to be associated with either mood and anxiety disorders. [42][43][44] To date, no definite information is available about the possible functional consequences of the TPH A218C polymorphism.…”
mentioning
confidence: 99%